The rule of law system for China’s marine security - Wang, Limei (Frontiers in Marine Science, 2024)
This paper examines the current status of China’s legislation on safeguarding sovereignty and security, resource security, navigation security, ecological security, and regulating law enforcement and judicial activities, and summarizes the characteristics of existing marine security legislation. This paper utilizes literature analysis and comparative analysis methods, under China’s Overall National Security Outlook, this paper proposes a path of improvement by consolidating marine-related norms, promoting the formulation of a basic law on the seas, refining the legal provisions on marine security, improving the marine data classification and grading system and safeguarding marine data security, and pushing forward the reform of the adjudication mechanism of the maritime courts to enhance the ability to actively safeguard the rights and interests of the oceans and seas through the use of the rule of law.